Replika AI Chatbot as a Tool for Enhancing ESP Business Vocabulary Acquisition: A Study on Polytechnic Students - Romadhon, Romadhon (SALEE: Study of Applied Linguistics and English Education, 2025)
This study is investigating the efficacy of using a Chatbot to enhance vocabulary acquisition in ESP, particularly in Business English. A total of 44 undergraduate students from a Polytechnic University in Indonesia participated in an experimental design. Later, they were divided into two groups: an experimental group that was engaged in continuous interaction with the chatbot for 14 weeks and the control group, following traditional instruction. Data collection was done through pre-tests, post-tests, and interviews. The experimental group significantly exceeded the control group in the post-test scores, according to the results; hence, the Chatbot is useful to support students in vocabulary learning. Such a fact was again asserted in the interview results, which showed the Chatbot's practicality and simplicity of usage for the participants in working with ESP vocabulary. Although positive, it has its limitation of a small sample size and focused on vocabulary alone. These limitations themselves suggest the need for further research. The future directions of such studies need to look into the larger vista of chatbot usage relating to other language skills also and the potential of this tool across educational settings and disciplines.